VO#048 Quotation for CC4 emulsion paint work on the ceiling rev.00 - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding the submission of quotation for CC4 emulsion paint work on the ceiling of BRACU new campus building.